2019
DOI: 10.3389/fnmol.2019.00272
|View full text |Cite
|
Sign up to set email alerts
|

DYRK1A Overexpression Alters Cognition and Neural-Related Proteomic Pathways in the Hippocampus That Are Rescued by Green Tea Extract and/or Environmental Enrichment

Abstract: Down syndrome (DS), caused by trisomy of chromosome 21, is the most common genetic cause of intellectual disability. We recently discovered that green tea extracts containing epigallocatechin-3-gallate (EGCG) improve cognition in mice transgenic for Dyrk1a (TgDyrk1A) and in a trisomic DS mouse model (Ts65Dn). Interestingly, paired with cognitive stimulation, green tea has beneficial pro-cognitive effects in DS individuals. Dual Specificity Tyrosine-Phosphorylation-Regulated Kinase 1A (DYRK1A) is a major candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 67 publications
6
26
0
Order By: Relevance
“…Our pro-cognitive treatment had a different effect on wild type mice than in Ts65Dn mice, confirming our previous observations in DYRK1A transgenic mice 7 . Around 44% of the proteins changing upon pro-cognitive treatments were common in wild type and trisomic mice, but with an opposite direction of change (Fig.…”
Section: Interactions (N) P-valuesupporting
confidence: 91%
See 3 more Smart Citations
“…Our pro-cognitive treatment had a different effect on wild type mice than in Ts65Dn mice, confirming our previous observations in DYRK1A transgenic mice 7 . Around 44% of the proteins changing upon pro-cognitive treatments were common in wild type and trisomic mice, but with an opposite direction of change (Fig.…”
Section: Interactions (N) P-valuesupporting
confidence: 91%
“…The pro-cognitive potential of green tea extracts and environmental enrichment was already shown in previous works 1,2,5,7,12,13 , but the molecular effect on the proteome and phosphoproteome remained elusive. We here show that these pro-cognitive treatments are able to restore more than 70% of the protein deregulation in trisomic mice, and induce compensatory mechanisms by acting on proteins of the same categories.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Its over-expression in different brain areas due to environmental insults or stress conditions reduces neural plasticity in neurons promoting cognitive problems and intellectual disability (166)(167)(168). Recent studies have demonstrated that some DYRK1A inhibitors such as the antioxidant Epigallocatechin gallate (EGCG) improve longterm outcomes related with memory and executive function in individuals with Down syndrome (166)(167)(168). Although it is currently under study, the inhibition of DYRK1A could improve the cognitive performance in pathologies associated to the loss of neuronal functions and plasticity, e.g., FASD, Autism, or Down Syndrome (169).…”
Section: Trophic Supportmentioning
confidence: 99%